Accuracy of Digital Models in Orthodontic Diagnosis - Törün Özer; Celal Genç (Galenos Yayinevi, 2008)
The overall objective of this study is to compare the measurements of plaster models and digital models on teeth with dental abnormalities. Pretreatment orthodontic models of 30 patients were selected from the archive of our university clinic. The inclusion criteria were as follows; 1. Full complement of permanent teeth including incisors, canines, premolars and first molars. 2. Dentitions with at least four or more teeth showing dental shape abnormalities (hypoplasia or restoration). Mesiodistal widths of each teeth from one molar to the other was measured. Available arch length, required arch length, arch deficiency and Bolton analysis was performed on each of the jaws. Although there were some statistically significant differences between the measurements, Bolton analysis and arch deficiency measurements did not demonstrate statistically significant difference between digital and plaster model measurements. Digital models could be used instead of plaster models for orthodontic diagnosis of a patient.